Biofabrication of Anisotropic Gold Nanotriangles Using Extract of Endophytic Aspergillus clavatus as a Dual Functional Reductant and Stabilizer - Verma V.C.; Singh S.K.; Solanki R.; Prakash S. (My University, 2025)
Biosynthesis of metal and semiconductor nanoparticles using microorganisms has emerged as a more eco-friendly, simpler and reproducible alternative to the chemical synthesis, allowing the generation of rare forms such as nanotriangles and prisms. Here, we report the endophytic fungus Aspergillus clavatus, isolated from surface sterilized stem tissues of Azadirachta indica A. Juss., when incubated with an aqueous solution of chloroaurate ions produces a diverse mixture of intracellular gold nanoparticles (AuNPs), especially nanotriangles (GNT) in the size range from 20 to 35 nm. These structures (GNT) are of special interest since they possess distinct plasmonic features in the visible and IR regions, which equipped them with unique physical and optical properties exploitable in vital applications such as optics, electronics, catalysis and biomedicine. The reaction process was simple and convenient to handle and was monitored using ultraviolet-visible spectroscopy (UV-vis). The morphology and crystalline nature of the GNTs were determined from transmission electron microscopy (TEM), atomic force spectroscopy (AFM) and X-ray diffraction (XRD) spectroscopy. This proposed mechanistic principal might serve as a set of design rule for the synthesis of anisotropic nanostructures with desired architecture and can be amenable for the large scale commercial production and technical applications. © 2010 The Author(s).